Non-Invasive Prenatal Testing: Review of Ethical, Legal and Social Implications - Haidar, Hazar; Dupras, Charles; Ravitsky, Vardit (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2016)
Non-invasive prenatal testing (NIPT) using cell-free fetal DNA (cffDNA) from maternal blood has recently entered clinical practice in many countries, including Canada. This test can be performed early during pregnancy to detect Down syndrome and other conditions. While NIPT promises numerous benefits, it also has challenging ethical, legal and social implications (ELSI). This paper reviews concerns currently found in the literature on the ELSI of NIPT. We make four observations. First, NIPT seems to exacerbate some of the already existing concerns raised by other prenatal tests (amniocentesis and maternal serum screening) such as threats to women’s reproductive autonomy and the potential for discrimination and stigmatization of disabled individuals and their families. This may be due to the likely upcoming large scale implementation and routinization of NIPT. Second, the distinction between NIPT as a screening test (as it is currently recommended) and as a diagnostic test (potentially in the future), has certain implications for the ELSI discussion. Third, we observed a progressive shift in the literature from initially including mostly conceptual analysis to an increasing number of empirical studies. This demonstrates the contribution of empirical bioethics approaches as the technology is being implemented into clinical use. Finally, we noted an increasing interest in equity and justice concerns regarding access to NIPT as it becomes more widely implemented.